Tradeoffs between units providing soil ecosystem services in multifunctional landscapes of the Orinoquia - Caro-Caro, Clara Inés; Bernal-Riobo, Jaime Humberto; Arango-Argoti, Miguel; Torres-Mora, Marco Aurelio (Frontiers in Environmental Science, 2022)
Ecological assessment of soil ecosystem services was made through indicators of provision of nutrients, amount of organic matter, and cation exchange capacity; and climate regulation, carbon storage, in the Orotoy river basin. As units that provide ecosystem services, mosaics of tropical humid forest cover, oil palm crops and cattle pastures were selected, persistent for 20 years, in windows located in the upper, middle and lower areas of the basin. Soil samples (896) were collected and analyzed in the laboratory for determining physical and chemical properties. The data were processed with the SPAW and R software. Indicators, ranging from 0 to 1, and tradeoffs were represented on a 1: 25.000 scale land cover map. It was found that in the indicator of carbon storage, the low zone obtained the highest average value (0.42); and the indicator of the ecosystem service of nutrient provision obtained close average values in the middle and lower zones, 0.33 and 0.44, correspondingly. In vegetation cover, the tropical humid forest presented the highest average values for the indicator of climate regulation (0,43). The established trade-offs from the valuation are: the upper zone is fundamental for water regulation and climate regulation throughout the basin; forest cover in the entire basin regulates the climate, oil palm crops and cattle pastures via fertilization, contribute to the surrounding forests, located in areas of less slope. In the mosaics of the multifunctional landscapes it was found that although the ecosystem services are related to the forming factors of the soil and the vegetation coverage, the influence of cultural practices on the soils is also evident; these determine trade-offs. The importance of including the ecosystem services of the soil in the processes of territorial ordering and management of landscapes like the one of the basin of the Orotoy river is verified, which in the current management scenario presents trade-offs between zones and coverages.